The conceptualization and enactment of critical thinking across diverse curricula in higher education - Bavli, Bunyamin; Ozdemir, Kubra (ELSEVIER SCI LTD, 2025)
The literature covers studies on the definition, understanding, perceptions, and teaching of Critical Thinking (CT); however, few studies focus on the conceptualization and enactment of CT across diverse curricula in higher education. The current study aimed to explore how faculty members conceptualize and enact CT across diverse curricula in higher education. As the study sought to examine the personal perspectives of individuals, a phenomenological inquiry was employed to capture the essence and meaning of their experiences. In line with this, a diverse group of university teachers from different academic backgrounds, holding various academic titles, and engaged in diverse curricula across various higher education institutions was included in the study. Data were collected through semi-structured, in-person, and online interviews. Thematic analysis was used for data analysis. Based on the analysis, two core themes emerged: Conceptualizing Critical Thinking (CT) Through Disciplinary Lenses and Teaching and Learning Process Management for CT Enactment. The results revealed valuable insights that can enhance both the conceptualization and effective implementation of critical thinking within higher education.
Keywords: Critical thinking; Diverse curricula; Higher education; Faculty members; DISPOSITIONS; Education & Educational Research